Presence of atypical porcine pestivirus (APPV) genomes in newborn piglets correlates with congenital tremor - Postel, Alexander (Sci Rep, 2016)
Pestiviruses are highly variable RNA viruses belonging to the continuously growing family Flaviviridae. A genetically very distinct pestivirus was recently discovered in the USA, designated atypical porcine pestivirus (APPV). Here, a screening of 369 sera from apparently healthy adult pigs demonstrated the existence of APPV in Germany with an estimated individual prevalence of 2.4% and ~10% at farm level. Additionally, APPV genomes were detected in newborn piglets affected by congenital tremor (CT), but genomes were absent in unaffected piglets. High loads of genomes were identified in glandular epithelial cells, follicular centers of lymphoid organs, the inner granular cell layer of the cerebellum, as well as in the trigeminal and spinal ganglia. Retrospective analysis of cerebellum samples from 2007 demonstrated that APPV can be found in piglets with CT of unsolved aetiology. Determination of the first European APPV complete polyprotein coding sequence revealed 88.2% nucleotide identity to the APPV sequence from the USA. APPV sequences derived from different regions in Germany demonstrated to be highly variable. Taken together, the results of this study strongly suggest that the presence of APPV genomes in newborn piglets correlates with CT, while no association with clinical disease could be observed in viremic adult pigs.